SUPPORTING PROPERTY INTERESTS ON LANDS RESERVED FOR FIRST NATIONS - Delorme, Michelle D (2022)
My concern within this thesis is the ongoing debate regarding the relationship of First Nations communities and private property rights. I do not advocate or share the view that private property rights on reserve are necessarily a colonial-based approach nor that they are a product of a continued Canadian project of genocide. Not all attempts to reconfigure land tenure rights for First Nations are attempts to eliminate Indigenous relationships with land or attempts to eliminate Indigenous peoples. The thesis shows that there are more options for private property on reserve than often realized. I examine the history of First Nation land management and provide a brief background of three land management regimes types: the Indian Act land management (IALM), First Nations land management (FNLM) and, more briefly, self-government land management (SGLM). While a direct comparison is not offered, I discuss the FNLM regime in greater detail and focus on the fact that it is a strong self-governing model for First Nations lands and resources. Despite the formality of land tenure offered through Certificates of Possession (CPs) under the Indian Act, many First Nations have not used CPs in the past. Instead, some have turned to an informal system of property rights often referred to as customary allotments. Some First Nations may have recognized these customary allotments and even recorded them in some fashion, but such property rights are not sanctioned under the Indian Act. This thesis will present some insight as to how those customary allotments have transitioned into a more formalized property system under the laws made by a First Nation pursuant to their land codes. Scholars have argued that an informal system lacks security of title due to poor documentation and often un-surveyed land holdings. I partly agree, though I also argue that land rights do not have to be absolute to be effective and the Framework Agreement provides for a better land registry scheme which is consistent and updated. It allows for First ...